Barriers to breast self-examination among Iranian women - Fariba Taleghani; Maryam Kianpour; Maryam Tabatabaiyan (Wolters Kluwer Medknow Publications, 2019)
Background: Breast cancer is a very common cancer in women which is diagnosable using inexpensive, accessible, and easy screening programs in the early stages of the disease. Culture, beliefs, and opinions of women affect adoption of screening techniques. Nursing professionals are supposed to be aware of such influencing factors. Therefore, this study was conducted to investigate barriers to breast self-examination (BSE) among women in Isfahan province. Materials and Methods: During a cross-sectional descriptive and correlational study in 2017, 1509 women in rural and urban areas of Isfahan province were selected using multistage sampling method. Data were collected by visiting homes, using a questionnaire, and conducting interviews and were analyzed using descriptive and analytical statistics. Results: The results showed that barriers consisted of lack of awareness about breast examination (p = 0.006), lack of awareness about BSE techniques (p < 0.001), and lack of training by personnel of healthcare centers (p = 0.016), which were significantly associated with residency areas (i.e., urban and rural areas). Moreover, women's educational level was significantly associated with 5 of 10 barriers and their occupation was significantly associated with 2 of 10 barriers to BSE. Conclusions: Among the several factors that may affect BSE, a part of them in Isfahan women act as obstacle that they are moderated by some demographic factors such as residency areas, education level, and occupation. Therefore, nursing plans and interventions aimed at developing BSE should be tailored to suit the unique demographic characteristics of women.